The Application of Inheritance Rights for Daughters Over Land in the Paswara Hindu Code: A Study in Karang Bang-Bang Subdistrict, Mataram City [Penerapan Hak Waris Anak Perempuan Atas Tanah Dalam Kitab Paswara Hindu: Studi di Kelurahan Karang Bang-Bang Kota Mataram] - Sakti, I Komang Pandita Reza; Mandala, Opan Satria; Efendi, Saparudin (Indonesia Berdaya, 2025)
Abstrac. Hindu society, especially the community in Karang Bang-bang sub-district, Mataram City, is a society that is thick and obedient to tradition, culture and customary law. The development of globalization and science and technology cannot immediately shake or change the customs and traditions of Hindu society. Customary law in the Hindu Paswara book greatly emphasizes the position of men in terms of inheritance and concerning family matters. When viewed from the perspective of roles in the family, in the current era women and men are almost contrasting. For example, in education, politics, government and so on, women have the same opportunities and even take on the same role. Likewise in the family, women can replace the position of men as head of the family and breadwinner if the condition of the man as a husband is no longer possible. Different conditions will be found in terms of inheritance law in the Hindu Paswara book. In general, women are not given the same opportunities as men, it can even be said that they have no right to participate in receiving inheritance or as heirs. So when viewed from the perspective of gender equality, it will give rise to a discriminatory impression against women. However, in principle women accept such conditions and do not consider this as something detrimental. Because this has become a habit that has been passed down from generation to generation to do. Abstrak. Masyarakat Hindu khususnya Masyarakat di kelurahan karang Bang-bang Kota Mataram merupakan masyarakat yang kental dan taat pada tradisi, budaya dan hukum adat. Perkembangan arus globalisasi dan ilmu pengetahuan serta teknologi, tidak semerta-merta dapat menggoyahkan apalagi merubah adat dan tradisi masyarakat Hindu. Hukum adat dalam kitab paswara Hindu sangat mengedepankan kedudukan laki-laki dalam hal pewarisan dan menyangkut masalah keluarga. Jika dilihat dari sisi peran dalam keluarga, pada era sekarang ini perempuan dan laki-laki hampir kontras. Misalnya dalam pendidikan, politik, pemerintahan dan sebagainya, kaum perempuan mempunyai kesempatan yang sama dan bahkan mengambil peran yang sama. Begitu juga dalam keluarga, perempuan dapat menggantikan posisi laki-laki sebagai kepala keluarga dan pencari nafkah apabila kondisi laki-laki sebagai suami sudah tidak memungkinkan lagi. Kondisi yang berbeda akan ditemukan dalam hal hukum waris dalam kitab Paswara Hindu. Secara umum kaum perempuan tidak diberikan kesempatan yang sama seperti laki-laki, bahkan dapat dikatakan tidak ada haknya untuk ikut menerima warisan atau sebagai ahli waris. Sehingga apabila ini dilihat dari kacamata kesetaraan gender, maka akan memunculkan kesan yang diskriminatif terhadap kaum perempuan. Namun demikian, pada prinsipnya perempuan menerima keadaan seperti itu dan tidak mengganggap ini sebagai suatu hal yang merugikan. Karena ini sudah menjadi kebiasaan yang secara turun temurun diwariskan untuk dilakukan.